Web-Based Outpatient Information System at RSUD Indramayu - Novianti, Dian; Hermanto, Nanang; Triono, Wahyu (Jurnal Improsci, 2024)
This outpatient information system is a system that is run on the hospital outpatient unit to support the service process provided to patients used by the units that provide services. This outpatient information system assists hospitals in implementing an integrated and structured digitization of patient medical record data. The study aimed to produce an outpatient information system that provides convenience to hospital staff and patients in the process of health services in the outpatient unit of RSUD Indramayu. In this study, the author uses a descriptive method, which is a method that describes a situation or problem that is currently happening based on the facts and data obtained and collected at the time of carrying out the research. Outpatient information system design uses document flow, system flow, tiered diagrams, context diagrams, data flow diagrams, conceptual data models, and physical data models. The implementation of this research uses the PHP programming language and MySQL database as well as writing the system design using DFD (Data Flow Diagrams), namely Data Flow Diagrams, FlowMap, Flowcharts, and Entity relationship diagrams (ERD). The result of the research is an integrated web-based outpatient information system application from the beginning to the end of outpatient services for patients.